Differential Physical and Mental Benefits of Physiotherapy Program Among Patients With Schizophrenia and Healthy Controls Suggesting Different Physical Characteristics and Needs - Szortyka, Michele Fonseca; Batista Cristiano, Viviane; Belmonte-de-Abreu, Paulo (Frontiers in Psychiatry, 2021)
Contrasting to several other severe illnesses, marked by inflammation and autoimmunity that now have potent and efficient treatments and even cure, schizophrenia is a disease still associated with poor outcome, incapacity, and social burden. Even after decades of research in brain and behavior, this illness is still associated with profound effects on both mental health and physical health, with recent studies showing that treatment is more efficient when associating drugs with psychological and physical treatments. Most of the studies measured the effect of physical intervention compared to usual care, and demonstrated positive effect as an add-on treatment. What remains unclear is the different effect of the same intervention in normal subjects in a sample of patients with the illness. The study aimed to evaluate the effect of physical intervention over motor functional capacity and mental health in schizophrenic patients (SCZ) compared to healthy controls (HC). The outcomes were a. functional capacity (by 6-minute-walk-test [6MWT]) b. body-flexibility-index (Wells’ bench), c. disease severity (by Brief Psychiatric Rating Scale [BPRS]), c. quality of life (by SF-36 questionnaire) and d. physical activity (Simple Physical Activity Questionnaire [SIMPAQ]). The intervention was associated with significant decrease of body mass index (BMI), blood pressure, disease severity and improvement in daily life activities. Unexpectedly, it was observed that schizophrenics, compared to match healthy controls, were at a lower level of performance in the beginning and remained below HC over the studied time despite similar physical intervention, and had different changes. The intervention had lower effects over physical capacity and better effects over quality of life and disease severity. The results confirm previous studies comparing patients receiving physical intervention, but suggest that they may receive different types of intervention, suited for their different baseline fitness, motivation and capacity to engage in physical effort over sustained time. Additionally, points to extended time of intervention of multidisciplinary treatment (physical and psychological - cognitive techniques) to improve outcomes in schizophrenia.